The correspondence of Thomas Reid - Reid, Thomas, 1710-1796 (Reid, Thomas, 1710-1796. Works. 1996., 2002)
This volume collects together all of the known letters to and from Thomas Reid in a fully annotated form. Letters already published by Sir William Hamilton and others have been re-edited, and approximately half of the letters included appear in print forthe first time.